2018
DOI: 10.4018/978-1-5225-3477-8.ch012
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences and the Development of Internet Addiction

Abstract: Internet addiction (IA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…This is in line with previous studies differentiating time spent online during The week and at weekends. Time spent online during both periods was predictive of PIU (47, 48), with higher results for time spent online during weekends and a stronger association with addiction [e.g., (4850)].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous studies differentiating time spent online during The week and at weekends. Time spent online during both periods was predictive of PIU (47, 48), with higher results for time spent online during weekends and a stronger association with addiction [e.g., (4850)].…”
Section: Discussionmentioning
confidence: 99%
“…Each factor contains two items rated on a five-point Likert scale ranging from ‘never’ to ‘always/almost always’ and total obtainable scores can range from 6 to 30, with higher scores indicating greater levels of PIU. The PIUQ-SF-6 has been previously shown to be psychometrically sound and has been utilized across several studies [e.g., 29 35 ]. In the present study, the PIUQ-SF-6 exhibited excellent internal consistency levels (Cronbach’s α = .84; McDonald’s ω = .90).…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, health and wellbeing problems related to such activities are of concern to healthcare providers (Kuss et al, 2014; Pontes et al, 2015; Lin et al, 2018e; Yang et al, 2018). In relation to growing health concerns, addiction to online and/or offline gaming has received increasing attention (Lemmens et al, 2009; de Palo et al, 2018) because many studies have demonstrated a variety of negative impacts are associated with it, including social anxiety (Weinstein et al, 2015), depression (Sariyska et al, 2015), poor emotional wellbeing (Rücker et al, 2015), and lowered life satisfaction (Macur and Pontes, 2018).…”
Section: Introductionmentioning
confidence: 99%